The Effect of the Yanbu'a Method on the Ability to Read the Qur'an in Class VII Students of SMP Negeri 2 Jalancagak - Saefullah, Selvia Ru’yatus; Ardilah, Novi (Journal International Dakwah and Communication, 2024)
This research was motivated by students’ low abilities to read Al-qur’an in learning Islamic religious education lesson. This is because the learning strategies are not varied using the Al-Qur'an learning method so that students are not interested and have difficulty to read the Al-Qur'an. This study aims to determine the implementation of the yanbu'a method, the reality of the ability to read the Al-Qur’an and the influence of the yanbu'a method on the ability to read the Al-Qur’an in VII grade students at SMP Negeri 2 Jalancagak. The study used quantitative method to analyze the data with the pre-experimental design pattern, namely one group design pretest and posttest. The sample of the research were students of VII D class at SMP Negeri 2 Jalancagak. The results of the data yanbu'a method at SMP Negeri 2 Jalancagak was based on a calculation of 50.95% for the first meeting, 61.58% for the second meeting and 75.32% for the third meeting; and the reality value of the ability to read the Qur'an was 3.24, which means in the medium state. Evidently, It was obtainned that the effect of the yanbu'a method on students’ reading Qur’an ability of the normality test reached a significance value of 0.00 < of ? = 0.05, meaning that the data is not normally distributed. Consequently, a non-parametric test is used with the Wilcoxon test to find out the influence of using the yanbu'a method on students’ reading Qur’an ability, the results shows that the value of (2-tailed) = 0.00 < ? = 0.05, it means that Ho is accepted. There is a difference between the pretest and posttest of the use of yanbu’a method on students’ reading Qur’an Ability. It can be concluded that there was an effect of the yanbu'a method on the ability to read the Qur’an.